HUMAN TALENT AS THE MAIN AXIS OF THE COMPANY - Veloz González, Ángel; Guillin Nuñez, Milton; Guillin Nuñez, Freddy (mktDESCUBRE, 2020)
This work was carried out by means of the bibliographic and quantitative method based on human talent, business, strategic planning and the product: in an organization, human talent is one of the most important factors within every company since it is The main responsible for the execution of the actions proposed in the direction of the proposed objectives and goals, the company is a productive unit dedicated to economic development within a society, strategic planning is the development of the different plans by the company or organization in order to achieve the objectives and goals set in the short, medium and long term, the product is a good that is offered to the market in order to meet the needs or desires of individuals, there is no doubt that people dedicate what best of his time and talent in search of the success of the organization, obtaining profitability by selling the products The realization of human talent is why companies make investments in training of their employees since having an efficient staff will obtain a competitive advantage in relation to their competitors in the same segment. The human talent at present within the llantera company “Galo Cargua Silva” has become a fundamental piece since these people are focused on the fulfillment of strategic planning, that is why people constitute the main asset of organizations since they contribute with knowledge, attitudes and skills and that makes companies more focused on the personal development of each of the employees and from there to start with productivity, in order to obtain business growth.